Impact of Psychiatric Information on Potential Jurors in Evaluating High-Functioning Autism Spectrum Disorder (hfASD) - Berryessa, Colleen M. (J Ment Health Res Intellect Disabil, 2015)
During a trial involving an offender with a mental disorder, jurors are often required to evaluate information on the disorder and its characteristics. This evaluation relies on how jurors understand and synthesize psychiatric and other evidence on the disorder and this information's impact on the case, an offender's culpability, and the rendered verdict. The importance of this evaluation is further highlighted when jurors are faced with evaluating a disorder that may be associated with criminal actions of diagnosed offenders, such as high-functioning autism spectrum disorder (hfASD). We designed a three-part survey to assess potential jurors' attitudes concerning an offender's diagnosis with hfASD in terms of perceptions and decisions surrounding legal and moral responsibility, personal characteristics of the offender, the introduction of psychiatric and genetic information, and the condition's influence on the facts of the case. A sample of 623 jury-eligible U.S. adults completed the survey. We found the majority of participants were influenced by the information provided on hfASD. Most respondents indicated that hfASD diagnosis should generally not affect the legal responsibility of an offender, but many reported the disorder as a mitigating factor when evaluating moral responsibility and legal consequences for criminal actions. Respondents reported favorable and sympathetic perceptions of individuals with autism and associated characteristics but were unsure, even after the presentation of psychiatric information on hfASD, if these disorders should be classified as “mental illness.” Further, the majority reported their views were in some way influenced by the fact that hfASD has potential genetic origins.